PENGARUH PENDEKATAN SCIENCE TECHNOLOGY ENGINEERING MATHEMATICS BERBANTUAN AUGMENTED REALITY TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS V SD - Nina Merliana, - (2023)
Elementary school students are currently expected to have high-order thinking skills, one of which is the ability to think creatively. By learning using the Science Technology Engineering Mathematics (STEM) augmented reality assited approach, students' creative thinking abilities can be developed through stages carried out in the learning. This study aims to determine the improvement and influence on students' creative thinking abilities between students who receive learning using STEM augmented reality assited approach and students who receive learning with conventional approach. This was done due to the low ability of students' creative thinking in science content learning with material on human movement organs. The research method used was a quasi-experimental design with a non- equivalent control group design and sampling using a purposive sampling technique. Based on the descriptive analysis, it was found that there was an increase in creative thinking of students who received learning with the STEM augmented reality assited approach, seen from the average N-gain for the control class as much as 0.0851 in the low category, while the average N-gain in the experimental class was an average N-gain as much as 0.3595 in the medium category. Therefore the STEM augmented reality assited approach is better than the conventional approach. In developing ability the results of this study also obtained the results that the STEM augmented reality assited approach had a positive influence as much as 49.7% on the creative thinking abilities of school students in the subject of human movement organs as indicated by the results of inferential analysis.